Inspired by Joel Tan

Geometry Level 5

Let x , y , z 0 x, y, z\geq 0 be reals such that x + y + z = 1 x+y+z=1 where points A ( x + y , x 2 + y 2 ) , B ( x + z , x 2 + z 2 ) A(x+y,x^2+y^2), B(x+z,x^2+z^2) , and C ( y + z , y 2 + z 2 ) C(y+z,y^2+z^2) are the vertices of a triangle.

If the maximum area of Δ A B C \Delta ABC can be expressed in simplest form as a b c \frac{a}{b\sqrt{c}} for coprime positive integers with c c square-free, what is the value of a + b + c a+b+c ?

Inspiration


The answer is 16.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Jason Hughes
Mar 11, 2015

First look at cases where x = y , y = z , x = z , x=y,y=z,x=z, or x = y = z x=y=z . The triangle Δ A B C \Delta ABC is a line or a point and has an area of zero. This would be the minimum area so to get the maximum area x y z x\neq y \neq z . We then restrict x , y x,y and z z to the following: 0 x < y < z 1. 0\leq x < y< z \leq 1.

We can then graph points A , B A, B and C C on a graph with axes u u and v v with general points ( u , v ) (u,v) . u u being the horizontal axis and v v being the vertical axis.

Point A A is at ( x + y , x 2 + y 2 ) (x+y,x^2+y^2) , Point B B is at ( x + z , x 2 + z 2 ) (x+z,x^2+z^2) , and Point C C is at ( y + z , y 2 + z 2 ) (y+z,y^2+z^2) .

If we extend a horizontal line at v = x 2 + y 2 v=x^2+y^2 . It intersects u = x + z u=x+z and u = y + z u=y+z at point B B^\prime and C C^\prime respectively.
If we extend a horizontal line at v = x 2 + z 2 v=x^2+z^2 it intersects u = y + z u=y+z at Point C C^{\prime\prime} .

B = ( x + z , x 2 + y 2 ) B^\prime = (x+z,x^2+y^2)

C = ( y + z , x 2 + y 2 ) C^\prime = (y+z,x^2+y^2)

C = ( y + z , x 2 + z 2 ) C^{\prime\prime} = (y+z,x^2+z^2)

Δ A B B , Δ B C C \Delta ABB^\prime, \Delta BCC^{\prime\prime} and Δ A C C \Delta ACC^{\prime\prime} all form right triangles. B B C C BB^{\prime} C^{\prime} C^{\prime\prime} forms a rectangle.

The area of Δ A B C \Delta ABC is Δ A C C Δ A B B Δ B C C B B C C | \Delta ACC^{\prime\prime} -\Delta ABB^\prime-\Delta BCC^{\prime\prime} - BB^{\prime} C^{\prime} C^{\prime\prime} | . It is absolute value since Point B B can lie above or below the line segment A C AC

Δ A C C = ( y 2 + z 2 ( x 2 + y 2 ) ) ( y + z ( x + y ) ) 2 = ( z 2 x 2 ) ( z x ) 2 \Delta ACC^{\prime\prime} =\frac{(y^2+z^2-(x^2+y^2))(y+z-(x+y))}{2}=\frac{(z^2-x^2)(z-x)}{2}

Δ A B B = ( x 2 + z 2 ( x 2 + y 2 ) ) ( x + z ( x + y ) ) 2 = ( z 2 y 2 ) ( z y ) 2 \Delta ABB^\prime =\frac{(x^2+z^2-(x^2+y^2))(x+z-(x+y))}{2}=\frac{(z^2-y^2)(z-y)}{2}

Δ B C C = ( y 2 + z 2 ( x 2 + z 2 ) ) ( y + z ( x + z ) ) 2 = ( y 2 x 2 ) ( y x ) 2 \Delta BCC^{\prime\prime} =\frac{(y^2+z^2-(x^2+z^2))(y+z-(x+z))}{2}=\frac{(y^2-x^2)(y-x)}{2}

B B C C = ( x 2 + z 2 ( x 2 + y 2 ) ) ( y + z ( x + z ) ) = ( z 2 y 2 ) ( y x ) BB^{\prime} C^{\prime} C^{\prime\prime} = (x^2+z^2-(x^2+y^2))(y+z-(x+z))= (z^2-y^2)(y-x) .

We get rid of the absolute value sign and just look for most positive or negative value of Δ A C C Δ A B B Δ B C C B B C C \Delta ACC^{\prime\prime} -\Delta ABB^\prime-\Delta BCC^{\prime\prime} - BB^{\prime} C^{\prime} C^{\prime\prime} .

= Δ A C C Δ A B B Δ B C C B B C C \Delta ACC^{\prime\prime} -\Delta ABB^\prime-\Delta BCC^{\prime\prime} - BB^{\prime} C^{\prime} C^{\prime\prime}

= ( z 2 x 2 ) ( z x ) 2 ( z 2 y 2 ) ( z y ) 2 ( y 2 x 2 ) ( y x ) 2 ( z 2 y 2 ) ( y x ) \frac{(z^2-x^2)(z-x)}{2} -\frac{(z^2-y^2)(z-y)}{2} -\frac{(y^2-x^2)(y-x)}{2}-(z^2-y^2)(y-x)

= ( z 2 x 2 ) ( z x ) 2 ( z 2 y 2 ) ( z y ) 2 ( z 2 y 2 ) ( y x ) 2 ( y 2 x 2 ) ( y x ) 2 ( z 2 y 2 ) ( y x ) 2 \frac{(z^2-x^2)(z-x)}{2} -\frac{(z^2-y^2)(z-y)}{2} -\frac{(z^2-y^2)(y-x)}{2}-\frac{(y^2-x^2)(y-x)}{2}-\frac{(z^2-y^2)(y-x)}{2}

Factoring yields

= ( z 2 x 2 ) ( z x ) 2 ( z 2 y 2 ) ( z y + y x ) 2 ( y 2 x 2 + z 2 y 2 ) ( y x ) 2 \frac{(z^2-x^2)(z-x)}{2} -\frac{(z^2-y^2)(z-y+y-x)}{2}-\frac{(y^2-x^2+z^2-y^2)(y-x)}{2}

= ( z 2 x 2 ) ( z x ) 2 ( z 2 y 2 ) ( z x ) 2 ( z 2 x 2 ) ( y x ) 2 \frac{(z^2-x^2)(z-x)}{2} -\frac{(z^2-y^2)(z-x)}{2}-\frac{(z^2-x^2)(y-x)}{2}

= ( ( z 2 x 2 ) ( z 2 y 2 ) ) ( z x ) 2 ( z 2 x 2 ) ( y x ) 2 \frac{((z^2-x^2)-(z^2-y^2))(z-x)}{2}-\frac{(z^2-x^2)(y-x)}{2}

= ( y 2 x 2 ) ( z x ) 2 ( z 2 x 2 ) ( y x ) 2 \frac{(y^2-x^2)(z-x)}{2}-\frac{(z^2-x^2)(y-x)}{2}

= ( y x ) ( z x ) ( y + x ( z + x ) ) 2 \frac{(y-x)(z-x)(y+x-(z+x))}{2}

= ( y x ) ( z x ) ( y z ) 2 \frac{(y-x)(z-x)(y-z)}{2} .

So the area of Δ A B C \Delta ABC is ( y x ) ( z x ) ( y z ) 2 \frac{(y-x)(z-x)(y-z)}{2} . First to maximize this you want to maximize y x , y-x, and z x z-x . This can be done by making x = 0 x=0 .

So the area of Δ A B C \Delta ABC is now y z ( y z ) 2 \frac{yz(y-z)}{2} with y + z = 1 y+z=1 . Substitute z z for 1 y 1-y .

Δ A B C = f ( y ) = y ( 1 y ) ( 2 y 1 ) 2 \Delta ABC = f(y)= \frac{y(1-y)(2y-1)}{2} for 0 < y < 1 0 < y <1 .

The maximum of this is when the derivative of f ( y ) f(y) equals zero.

f ( y ) = 3 y 2 + 3 y 1 2 = 0 f^{\prime}(y)= -3y^2+3y-\frac{1}{2}=0 at y = 3 3 6 y= \frac{3-\sqrt{3}}{6} or 3 + 3 6 \frac{3+\sqrt{3}}{6} .

f ( 3 3 6 ) = 1 12 3 f( \frac{3-\sqrt{3}}{6}) = -\frac{1}{12\sqrt3} .

f ( 3 + 3 6 ) = 1 12 3 f( \frac{3+\sqrt{3}}{6}) = \frac{1}{12\sqrt3} .

This means that the maximum area of Δ A B C \Delta ABC is 1 12 3 \frac{1}{12\sqrt3} .

Thus a = 1 , b = 12 , c = 3 a=1,b=12,c=3 and a + b + c = 16 a+b+c=\boxed{16}

Alternatively we can use the shoelace theorem to instantly obtain the formula for the area:

P = 1 2 i = 1 n x i y i + 1 x i + 1 y i P=\frac { 1 }{ 2 } { |\sum _{ i=1 }^{ n }{ { x }_{ i }{ y }_{ i+1 }-{ x }_{ i+1 }{ y }_{ i } } | } where ( x i , y i ) \left( { x }_{ i },{ y }_{ i } \right) are the coordinates of the vertices of the polygon.

We can now substitute, obtaining the following:

P = 1 2 ( x + y ) ( x 2 + z 2 ) + ( x + z ) ( y 2 + z 2 ) + ( y + z ) ( x 2 + y 2 ) ( x + z ) ( x 2 + y 2 ) ( y + z ) ( x 2 + z 2 ) ( x + y ) ( x 2 + y 2 ) P=\frac { 1 }{ 2 } { |\left( x+y \right) \left( { x }^{ 2 }+{ z }^{ 2 } \right) +\left( { x }+{ z } \right) \left( { y }^{ 2 }+{ z }^{ 2 } \right) +\left( y+z \right) \left( { x }^{ 2 }+{ y }^{ 2 } \right) -\left( x+z \right) \left( { x }^{ 2 }+{ y }^{ 2 } \right) -\left( y+z \right) \left( { x }^{ 2 }+{ z }^{ 2 } \right) -\left( x+y \right) \left( { x }^{ 2 }+{ y }^{ 2 } \right) | }

Which simplifies to P = 1 2 ( x y ) ( x z ) ( y z ) P=\frac { 1 }{ 2 } { |\left( x-y \right) \left( x-z \right) \left( y-z \right) | } .

Personal Data - 5 years, 11 months ago

Why must ( y x ) ( z x ) ( y z ) (y-x)(z-x)(y-z) attain its maximum when y x y-x and z x z-x are maximized? What if there was an x x slightly bigger than 0 0 such that those two expressions are made a little smaller but in turn y z y-z can be made bigger, making the entire expression bigger?

My concern is that the step was not rigorous enough.

Daniel Liu - 5 years, 11 months ago

How you can directly tell that you have to take x=0 for maximization. The logic is not at all correct. Why can't i maximize x-y, x-z, and y-z simultaneously.

Reetun Maiti - 5 years, 6 months ago
Daniel Liu
Jun 24, 2015

Consider the triangle with vertices ( x , x 2 ) (x, x^2) , ( y , y 2 ) (y,y^2) , and ( z , z 2 ) (z, z^2) . Note that its medial triangle maps to A B C \triangle ABC through a homothety with a factor of 2 2 w.r.t the origin, so our new triangle has the same area as A B C \triangle ABC , so we can just look at this new triangle.

By the Shoelace theorem, we see that the area is [ A B C ] = 1 2 c y c x 2 y c y c x y 2 [ABC]=\dfrac{1}{2}\left|\sum_{cyc}x^2y-\sum_{cyc}xy^2\right| which factors as 1 2 ( x y ) ( y z ) ( x z ) \dfrac{1}{2}|(x-y)(y-z)(x-z)| Now note that y x z y\ge x\ge z and x y z x\ge y\ge z are equivalent because of the absolute value, so WLOG x y z x\ge y\ge z which means the expression is positive and we just need to maximize 1 2 ( x y ) ( y z ) ( x z ) \dfrac{1}{2}(x-y)(y-z)(x-z) . Applying BW let y = z + u y=z+u and x = z + u + v x=z+u+v where z , u , v z,u,v are non-negative reals so our question is: given 3 z + 2 u + v = 1 3z+2u+v=1 maximize 1 2 u v ( u + v ) \dfrac{1}{2}uv(u+v) Clearly then we must have z = 0 z=0 and thus v = 1 2 u v=1-2u and we want to maximize 1 2 u ( 1 2 u ) ( 1 u ) \dfrac{1}{2}u(1-2u)(1-u) given 0 u 1 2 0\le u\le \dfrac{1}{2} But taking a derivative gives that the maximum happens at 1 2 u ( 1 2 u ) ( 1 u ) = 1 12 3 \dfrac{1}{2}u(1-2u)(1-u) =\boxed{ \dfrac{1}{12\sqrt{3}}} and we're done.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...